I'm not sure what you have to do... They seem in a pretty simple form. Maybe you want something like the following..
3.f(x) = x(x-6)
x(x-6) = -6x = -6x+9-9 = ( -6x+9)-9 = -9
For this one, note first that (x - 1)(x + 1) = x^2 - 1. Then multiply this by the product of the other two linear factors, x^2 + x - 12. Multiply that through by the -2, and you're done.
You can multiply the polynomial factors in any order you like, but it might be quickest to multiply the x + 2 by the x + 4, and then multiply the result by the x + 1.
Take the x through the parentheses, and you're done.